(untitled) (Лучшие интеллектуальные исследования, 2025)
Аннотация: решения задачи подготовки бакалавров физической культуры и спорта к тренерской деятельности по игровым видам спорта с детьми дошкольного возраста . Annotation: solutions carried out on the problem of training Bachelors of physical education and sports for coaching activities in play sports with preschool children .